Implementation of New Workflow Layout for Capstone Design Project - Hanna Masâ€™aud, Nurul; Ghazali, Hanipah; Ridzuan Mohamed Rashid, Mohamad; ., . (International Journal of Engineering and Technology, 2018)
In completing a capstone design project, students were allowed to use all facilities in a mechanical workshop (including machining area, assembly area, and welding area). However, the main problem was they had a very limited space and time to do their work due to the poor arrangement of raw material, machines, and tools. Therefore, this study was conducted to create a systematic process workflow layout. After implementing the new improvement of process workflow layout, a time study analysis and a satisfactory survey were conducted. The study found that total average transportation time could be reduced from 313sec to 102sec with 67.14% of reduction. As for satisfactory survey, it was found that most of the users were satisfied with the new process workflow layout; 7.41% of the users found it very convenient, 75.93% convenient and 18.52% moderately convenient.Â Â